2008
DOI: 10.4161/epi.3.2.6034
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to maternal depression, neonatal methylation of human glucocorticoid receptor gene (NR3C1) and infant cortisol stress responses

Abstract: Methylation status of the human NR3C1 gene in newborns is sensitive to prenatal maternal mood and may offer a potential epigenetic process that links antenatal maternal mood and altered HPA stress reactivity during infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

64
1,016
7
27

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,279 publications
(1,130 citation statements)
references
References 50 publications
64
1,016
7
27
Order By: Relevance
“…Fourth, information on exposure to trauma prior to treatment was not available for this sample. Traumatic experiences in childhood have been demonstrated to have lasting effects on DNA methylation of both the FKBP5 and GR genes 11, 12, 14, 15, 16, 17. Therefore, we are unable to make any conclusions regarding other environmental factors that may have influenced baseline DNA methylation and subsequent changes in DNA methylation during active treatment.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Fourth, information on exposure to trauma prior to treatment was not available for this sample. Traumatic experiences in childhood have been demonstrated to have lasting effects on DNA methylation of both the FKBP5 and GR genes 11, 12, 14, 15, 16, 17. Therefore, we are unable to make any conclusions regarding other environmental factors that may have influenced baseline DNA methylation and subsequent changes in DNA methylation during active treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Studies of early experiences in rats found that DNA methylation of the GR promoter region was altered by maternal care, which in turn was associated with GR expression and HPA responses to stress 12. In humans, stressful life events (e.g., trauma and abuse) have been associated with higher DNA methylation at the GR promoter region13, 14, 15, 16, 17, 18 as well as differential GR expression and biological markers of HPA‐axis activity, such as salivary cortisol 13, 14. Furthermore, GR methylation has been implicated in the development of PTSD following trauma 19.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that hypermethylation of the NR3C1 gene influences cortisol response, infant behavior and self-regulation. 39,40 Interestingly a recent experimental study demonstrated that exposure to arsenic in utero lowers the activity of the glucocorticoid receptor pathway and these changes were maintained into adolescence of the mouse model. 41 However, further studies are needed to confirm whether these biological findings influence behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We selected candidate genes based on the results of prior work in rodents, primates, and humans, which found that exposure to various psychosocial stressors was associated with DNAm in genes related to stress reactivity, including AVP, 19 BDNF, 20,21 CRF, 22 FKBP5, 23 GR, [24][25][26][27][28][29] OXTR, 30 and SLC6A4, [31][32][33][34] and inflammation, including CD1D, CCL1, F8, IL8, KLRG1, LTA4H, NLRP12, PYDC1, SLAMF7, TLR1, and TLR3. 35 Stress reactivity and inflammation have been hypothesized to mediate the impact of social circumstances on health and are therefore reasonable candidates for investigation of SES effects on DNAm processes.…”
Section: Introductionmentioning
confidence: 99%